Volumetric, acoustic and viscometric behaviour of dipotassium hydrogen phosphate and disodium hydrogen phosphate in aqueous solution of N-acetyl glycine at different temperatures. (March 2016) - Kumar, Harsh; Singla, Meenu; Mittal, Heena
Highlights: Densities, speeds of sound, viscosities of phosphate salts in aqueous N-acetyl glycine. Large values of partial molar volume for dipotassium hydrogen phosphate. Partial molar volume of transfer are positive for phosphate salts. Positive B -coefficient values indicate ion–solvent interactions. Abstract: Densities, speeds of sound and viscosities of dipotassium hydrogen phosphate (DPHP) and disodium hydrogen phosphate (DSHP) in aqueous solutions of N-acetyl glycine (AcGly) are reported at different temperatures. Densities and speeds of sound have been used to calculate apparent molar volume, apparent molar isentropic compression, partial molar volume, partial molar isentropic compression, partial molar volume of transfer, partial molar isentropic compression of transfer and partial molar expansivity. Pair and triplet interaction coefficients have also been calculated. Experimental viscosities have been used to determine B -coefficients. Further pair and triplet interaction coefficients have also been calculated. The results are discussed in terms of solute–solvent interactions.